Productivity Scenedesmus sp. in Various Cultivation Media - Firmansyah, Bagus; Andriani, Yuli; Herawati, Titin; Zahidah, Zahidah (Hasanuddin University, 2024)
Scenedesmus sp. is one of the microalgae that is used as natural food for fish seeds or larvae. Scenedesmus sp. contains 8-56% protein, 10-52% carbohydrates, 2-40% fat, and 3-6% nucleic acid. Scenedesmus sp. also contains fatty acids in the form of lauric acid (0.22%), myrsiric acid (0.34%), linolenic acid (16.16%), glycerol trilaurate (3.73%), and vanil laurate (35.52%). Cultivation of Scenedesmus sp. can be done using inorganic fertilizer or waste water media. The types of inorganic fertilizer commonly used for cultivation are urea, KCL, TSP, Intermediate, Raja Bandeng brand. Meanwhile, waste water media can be used for cultivating Scenedesmus sp. namely tofu liquid waste water, milk waste water, bean sprout extract media, textile waste water. The results of cultivation in this media have an influence on the productivity of Scenedesmus sp.